diversity - Grigoryeva, Elena (project baikal, 2025)
Our salvation, the salvation of all mankind, lies in diversity. Isaac Asimov, “Lucky Starr” Curiouser and curiouser… Lewis Carroll The world is becoming more diverse. But the value of multicolored reality is not realized immediately, having many recurrences of the opposite tendency. Disputes of diverse opinions and styles arouse suspicion, and “eclecticism” (in ancient Greece, a method of thinking that combines the best elements of different schools) has become a pejorative label. Nevertheless, PB follows the trend of an increasingly complex world. In this issue, there is artificial intelligence and a genuine Intellectual (a selection about AGR), reflections on the peculiarities of architectural thinking and the role of metaphor in architecture... After decades of the rule of precast reinforced concrete, wooden housing construction is diversifying the appearance of modern cities and strangely combines with ventilated, a priori temporary facades. Agglomerations harmoniously coexist with villages. The debate over the issue of stylistic diversity has been raging over and over again. Should architecture develop freely in accordance with advances in technology and modern demands, or should the process be regulated and dictated by the use of style, for example, in the design of government buildings, as US President Donald Trump insistently declares in his next edict on architecture dated August 28? Is it possible to define a single national architectural style in a multinational country, or long live diversity and let all the flowers bloom? There are many questions. What exactly is the place (undoubtedly significant) occupied by the heritage of various eras in the common spectrum – the Russian Far East, China and medieval Armenia, monuments from the USSR times in Kazakhstan? Besides, at the anniversary ZVS festival, the PB discussion club was dedicated to the fate of the Irkutsk legacy of Soviet modernism. Our difficult time calls us to carefully preserve and multiply diversity in all dimensions – in time, in the space of countries and peoples, in the style and methods of cognition of the world. Elena Grigoryeva